ЁШ ВОЛЕЙБОЛЧИЛАРДА АЙРИМ ЖИСМОНИЙ ВА ФУНКЦИОНАЛ КЎРСАТКИЧЛАРНИ ТУРЛИ ЮКЛАМАЛАР ТАЪСИРИДА ЎЗГАРИШ ДИНАМИКАСИ - Қалжанов, П.У. (SCIENCE and SOCIETY, 2022)
The analysis of results of the research of the level of development of special efficiency of young volleyball players of 15-16 years and the possibility of its preservation in the course of the game is presented in article. It is established that such level of the studied qualities decreases in process of end of game parties more and more. The opinion is put forward that such dynamics of change of these qualities demonstrates instability of their status.